2011
DOI: 10.1103/physreva.83.042340
|View full text |Cite
|
Sign up to set email alerts
|

Semioptimal practicable algorithmic cooling

Abstract: Algorithmic Cooling (AC) of spins applies entropy manipulation algorithms in open spin-systems in order to cool spins far beyond Shannon's entropy bound. AC of nuclear spins was demonstrated experimentally, and may contribute to nuclear magnetic resonance (NMR) spectroscopy. Several cooling algorithms were suggested in recent years, including practicable algorithmic cooling (PAC) and exhaustive AC. Practicable algorithms have simple implementations, yet their level of cooling is far from optimal; Exhaustive al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…This idea was improved by adding contact with a heat-bath to extract entropy from the system [5], a process known as Heat-Bath Algorithmic Cooling (HBAC). Based on this work, many cooling algorithms have been designed [6][7][8][9][10][11]. HBAC is not only of theoretical interest, experiments have already demonstrated an improvement in polarization using this protocol with a few qubits [12][13][14][15][16][17][18], where a few rounds of HBAC were reached; and some studies have even included the impact of noise [19].…”
Section: Introductionmentioning
confidence: 99%
“…This idea was improved by adding contact with a heat-bath to extract entropy from the system [5], a process known as Heat-Bath Algorithmic Cooling (HBAC). Based on this work, many cooling algorithms have been designed [6][7][8][9][10][11]. HBAC is not only of theoretical interest, experiments have already demonstrated an improvement in polarization using this protocol with a few qubits [12][13][14][15][16][17][18], where a few rounds of HBAC were reached; and some studies have even included the impact of noise [19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this new idea, many practical cooling algorithms have been designed [11][12][13][14][15]. In short, HBAC purifies qubits by applying alternating rounds of entropy compression and pumping out entropy from the system of interest to a thermal bath.…”
Section: Theory Of Algorithmic Coolingmentioning
confidence: 99%
“…This provides 10 protons that are hyperfine coupled to the electron and are spectrally distinguishable through ENDOR. Nitrogen can be isotopically labelled as 15 N to provide an additional strongly coupled nuclear spin. This spin system therefore affords the possibility of implementing HBAC with up to 12 qubits [39].…”
Section: Prospects: Exploiting Larger Hilbert Spaces and The High Fiementioning
confidence: 99%
“…Here, the reset qubits periodically release their excess entropy to a heat-bath so that higher cooling of the computation qubit can be achieved by constructive iterations of AC. Since then, several HBAC algorithms have been proposed [10][11][12][13][14] and numerous experimental studies have also been reported [15][16][17][18][19][20][21] which use three or five qubit entropy compression circuits as the building block for AC. More recently asymptotic bounds for HBAC algorithms have been estimated numerically by Raeisi et * mahesh.ts@iiserpune.ac.in al.…”
Section: Introductionmentioning
confidence: 99%